Community forest management led to rapid local forest gain in Nepal: A 29 year mixed methods retrospective case study. (March 2023) - Smith, Alexander C.; Hurni, Kaspar; Fox, Jefferson; Van Den Hoek, Jamon
Abstract: Despite widespread implementation of community forest (CF) management over the last 40 years, limited knowledge exists on CF-level processes that link introduction of CF management to long-term forest cover change. CF management has been widely adopted in Nepal but research on effects of CF management on forest cover change often lacks long-term forest cover data and does not attempt to directly link changes in local forest cover with forest management decisions by local forest users. This study used a mixed methods approach integrating a 29 year-long satellite record of annual forest cover (1988–2016) and local interview data from 2018 to 2020 across eight CFs in Nepal to evaluate the spatially explicit impacts of CF management on long-term forest cover change. Information on historical forest management practices and forest conditions were collected from qualitative open-ended interviews with 28 CF user group managers, forest management records, and field observations. Annual forest cover change from 1988 to 2016 was measured using Landsat satellite time series data. For each CF, the impacts of local forest management decisions on forest cover trends were then characterized before and after the local introduction of CF management. Although study CF user groups had a wide range of initial forest cover (11–93%) before CF management, forest cover increased in all eight study sites under CF management to between 58% and 99% by 2016. Forest cover gains were evident during an informal period of CF management that preceded formal registration and management in most CFs and were maintained over the ensuing period of formal CF management. Interview data show that forest cover gains directly followed the introduction of informal and formal CF management activities such as tree planting, forest patrols, and grazing regulations. In our case study CFs, the early success of CF management motivated the continued investment in forest management leading to long-term forest conservation. This study demonstrates that CF management has been effective at conserving and expanding forest cover in community forests, and that yearly forest change and management data can be used to assess both the immediate impact and long-term sustainability of CF management. Highlights: Mixed methods analysis used to reveal impact of community forestry on forest cover. A 29-year remote sensing analysis links forest change to community management. Forest cover gain was directly attributed to community forestry management activities. Forest cover and management data effectively assessed short/long-term sustainability. Community participation increases forest conservation and expansion.